2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32565
|View full text |Cite
|
Sign up to set email alerts
|

Creativity Activities in a Design Course Fail to Elicit Gains in Creativity Over and Above those Elicited by the Design Course Itself

Abstract: Biology and Chemistry from St. Francis College in Ft. Wayne, Indiana and his Ph.D. in Physiology from the University of Arizona. Will did his postdoctoral training in Molecular Biophysics at the University of Vermont. His research interests include novel assessments of educational efficacy, the molecular basis of cell movement, and the mitigation of infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Similarly, a study conducted by Anderson, Anderson and Jensen (2019) found that using creativity practice exercises in capstone classes showed an improvement in the Creativity Index determined by the Torrance Tests of Creative Thinking (TTCT) Figural Test [20]. Contrarily, a study completed by Guildford in 2019 found that creativity exercises with non-academic rewards did not have a significant improvement in creativity than the design course already provided [18].…”
Section: Introduction/ Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study conducted by Anderson, Anderson and Jensen (2019) found that using creativity practice exercises in capstone classes showed an improvement in the Creativity Index determined by the Torrance Tests of Creative Thinking (TTCT) Figural Test [20]. Contrarily, a study completed by Guildford in 2019 found that creativity exercises with non-academic rewards did not have a significant improvement in creativity than the design course already provided [18].…”
Section: Introduction/ Motivationmentioning
confidence: 99%
“…Another approach to implementing creativity is to implement a creativity intervention, or warm-up before a task, assignment, or problem. Creative interventions have been used in a few studies before, with varying results [18,19,20]. In a study done by Worinkeng, Summers and Joshi, participants that completed a presketching activity before a design problem proved to come up with more novel solutions.…”
Section: Introduction/ Motivationmentioning
confidence: 99%